KONTRIBUSI SUPERVISI AKADEMIK KEPALA SEKOLAH DAN MOTIVASI KERJA GURU TERHADAP KINERJA MENGAJAR GURU - Mulyani Wijayanti, Fransiska Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This research uses survey methode with quantitative approach. The sample is taken from the whole number of population which are 90 teachers. The area of the research is conducted in Government Vocational High School of Business Management Study Program Pontianak. The object of this research is the teachers civil servants who have got the sertification. The techniques of analizes which are used are describtive and inferential analizes. The result of the research finds that the contribution of school principal academic supervision and teacher work motivation toward the teacher teaching performance is 26,10% and the rest of 73,90% is influenced by other factors which have not been researched yet; such as, ability, intectual, attitude, work experience, facility, leadership style, and work environtment, and etc. It is recommended that (1) the implementation of school principal academic supervision is still weak so it need to be conducted by the school principal regularly and continuously by using individual and group techniques, (2) The teacherâ€™s extrinsick/external motivation needs to be developed with openess minded and willingness of welcomed advices, and (3) the implementation of teaching and learning prosess have not been running optimally yet, so it need to be improved as well as the teacherâ€™s ability to give follow up on learning evaluation in order to reach the maximum teaching and learning target. Â Keywords : Academic Supervision , Teacher Work Motivation , Teacher Performance